Comparison of fatigue criteria for combined bending-torsion loading of nitrided and virgin specimens - Major, S.; Papuga, J.; Hornikova, J.; Pokluda, J. (Проблемы прочности, 2008)
This work deals with fatigue life of plasma-nitrided and virgin specimens made of a low-alloy high strength steel. Specimens were subjected to an in-phase combined bending-torsion loading. The plasma-nitrided specimens exhibited a significantly improved fatigue resistance. The criterion proposed by McDiarmid was found to be the most precise in the fatigue life prediction fo r virgin specimens. On the other hand, the Matake criterion was the most successful fo r nitrided specimens. Исследована усталостная долговечность азотированных в плазме образцов и исходных образцов из низколегированной высокопрочной стали. Испытания образцов проводились при синфазном совмещенном изгибе с кручением. Показано, что азотированные в плазме образцы обладают более высокой усталостной стойкостью. Установлено, что для образцов в исходном состоянии наибольшая точность прогнозирования усталостной долговечности обеспечивается при использовании критерия, предложенного Мак-Диармидом. С другой стороны, для азотированных образцов наиболее подходящим оказался критерий Матаке.